TAHLIL AL MUFRODATI AL 'ARABIYYATI AL DAKHILATI ILA AL LUGHATI AL URDIYYATI - anisa Octaviani (Nazharat: Jurnal Kebudayaan, 2021)
This study discusses the analysis of Arabic vocabulary into Urdu. Urdu is one of the languages in India and is the official language in Pakistan and Bangladesh. Urdu language with its development is heavily influenced by Arabic because during the Islamic era, its expansion was very rapid in the Indian Subcontinent.The purpose of this study is to: ) Knowing what Arabic vocabulary is used by Urdu in the Google Play Store application ) Knowing the changes in writing Arabic vocabulary into Urdu. ) Knowing the sound changes in Arabic vocabulary into Urdu. ) Knowing the changes in the meaning of Arabic vocabulary into Urdu. The type of research used is qualitative research. It can be concluded from the results of this study: ) There are Arabic vocabulary that goes into Urdu on the Google Play Store application ) There is a change in writing Arabic vocabulary that goes into Urdu ) There is a change in the sound of Arabic vocabulary that goes into Urdu. in urdu ) There is a change in the meaning of arabic vocabulary into urdu.